(untitled) (Praxis Educativa, 2017)
The results of five focus groups with Adult High School (AHS) students to explore and characterize their interests to attend this institution are presented. Their Social Representations (SR) about the social and personal function of the AHS are explored. As a first approach to this issue, an inductive categorization was made from analysis of the printed transcript of the conversations, and the software Atlas.ti®. The results indicate that the SR identified do not allow these students to critically analyze if the school guides them to achieve their objectives. The results constitute the basis for conducting a survey. Also, the results indicate the need to consider the interests and SR of adults among the factors that must be considered to rethink the AHS.